Harry Potter and the deathly hallows - Rowling, J. K. (Bloomsbury London, 2018)
"Harry has been burdened with a dark, dangerous and seemingly impossible task: that of locating and destroying Voldemort's remaining Horcruxes. Never has Harry felt so alone, or faced a future so full of shadows. But Harry must somehow find within himself the strength to complete the task he has been given. He must leave the warmth, safety and companionship of The Burrow and follow without fear or hesitation the inexorable path laid out for him."--Publisher's description